Access barriers to healthcare services among the Fulani population in Ghana: a qualitative study in the Sissala East Municipality - Richard Abeiku Bonney; Daniel Opoku; Kofi Akohene Mensah; John Humphrey Amuasi; Ebenezer Dassah; Benjamin Obukowho Emikpe; Ruth Waitzberg (BMC Health Services Research)
Abstract Background Access to healthcare services is at the center of every health system. Research to understand access to healthcare services for the Fulani in Ghana is limited. Efforts have mainly focused on the confrontations between the Fulani herders and the communities. The study aimed to explore what access barriers exist among the Fulani vulnerable population in Ghana; this will contribute to the understanding of access to healthcare services for a vulnerable population, who are also prone to possible transmission of diseases from human-animal connections, and requiring global health interventions. Methods This is an explorative study using qualitative methods to investigate how the Fulani population access healthcare services in the Sissala East Municipality, Ghana. From 17 to 30 September 2022, interviews were conducted using an interview guide among 11 individuals sampled purposively based on the criteria that, the individual is a Fulani or healthcare professional, resides in and around the study area, and is 18 years or older. Thematic content analysis was used for the analysis. Results Contrary to the widely held view of the Fulani population being typically conservative, they displayed positive healthcare-seeking behavior and acceptance of modern healthcare services. And despite their nomadic lifestyle, physical accessibility of healthcare services has not been a challenge given that they can even reach a health facility via mobile phones (mHealth) as well as via other means of transport (e.g., motor bike). However, access barriers to healthcare are influenced mainly by financial constraints and gender roles. They rely on health insurance for healthcare coverage, but co-payments and difficulties in enrollment pose serious healthcare affordability challenges. They require access to health information to improve their knowledge on health-related issues as well. Conclusion This study reveals that the main barrier to healthcare access among the Fulani is affordability and gender-specific roles. However, they are also utilizing innovative mobile technologies to assist in seeking healthcare against the potential barrier of their nomadic lifestyle. Community engagement and policy measures to improve the coverage of the national health insurance scheme are required to improve healthcare access among the Fulani vulnerable population.